2020
DOI: 10.1186/s12891-020-3085-z
|View full text |Cite
|
Sign up to set email alerts
|

Forced treadmill running reduces systemic inflammation yet worsens upper limb discomfort in a rat model of work-related musculoskeletal disorders

Abstract: Background: Musculoskeletal disorders can result from prolonged repetitive and/or forceful movements. Performance of an upper extremity high repetition high force task increases serum pro-inflammatory cytokines and upper extremity sensorimotor declines in a rat model of work-related musculoskeletal disorders. Since one of the most efficacious treatments for musculoskeletal pain is exercise, this study investigated the effectiveness of treadmill running in preventing these responses. Methods: Twenty-nine young … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Since we have previously shown that prolonged performance of high intensity repetitive tasks induce pathological changes in flexor digitorum tendons [ 15 , 52 ], we next examined for such changes in this study. We first examined for changes in mid- to distal flexor digitorum tendon proper (interior) regions and saw more rounded cells and moderately enhanced cellularity and collagen fibril disorganization in TASK-Ac tendons, relative to the other groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since we have previously shown that prolonged performance of high intensity repetitive tasks induce pathological changes in flexor digitorum tendons [ 15 , 52 ], we next examined for such changes in this study. We first examined for changes in mid- to distal flexor digitorum tendon proper (interior) regions and saw more rounded cells and moderately enhanced cellularity and collagen fibril disorganization in TASK-Ac tendons, relative to the other groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pro-inflammatory processes are required for proper muscle repair and clearance of injury-induced debris [ 54 56 ]. In this model, CD68+ macrophages and pro-inflammatory cytokines elevate in upper extremity nerves, muscles and tendons either immediately after the initial training period (task week 0) during which rats ramp up from naïve to high force lever pulling, or by task week 3 [ 7 , 10 , 12 , 40 , 52 ]. The post-training task week 0 is also the peak production point of several pro-inflammatory cytokines (such as, muscle CCL2/MCP-1 and IL-18), while task weeks 3 to 6 are the peaks for others (such as, muscle and serum TNF-α) [ 7 , 10 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…released directly from the involved skeletal muscle(s) and tendon(s) or the surrounding fascial tissues, causing tissue damage and fibrosis [25]. Enhanced intraneural inflammation and nerve fibrosis were shown in the high-repetition high-force treadmill group compared to the control group [26]. It was also shown to correlate with increasing pain and tingling.…”
Section: Discussionmentioning
confidence: 99%
“…Although the anti-inflammatory effects of exercise are largely systemic and attributed to changes in “non-muscle” factors/cells (e.g., reduced adipose tissue, macrophages, T- and NK cells and activation of the HPA axis) [ 210 , 211 ], the contracting muscle cells themselves produce IL-6, which inhibits TNF and stimulates the production of anti-inflammatory cytokines [ 212 ]—highlighting the dual systemic and local impact of exercise on inflammation, with potentially broad therapeutic implications. For instance, the potent anti-inflammatory effects of aerobic whole-body exercise [ 191 , 213 ] are accompanied by reduced musculoskeletal fibrosis [ 27 ] (unless injured tissues are loaded [ 214 ]) and improvements in psychological wellbeing and lifestyle health [ 215 , 216 ]. Other factors might have similar multidirectional effects.…”
Section: New Opportunities To Understand and Enhance The Effects Of Treatmentsmentioning
confidence: 99%